DEFINITION le_not_lt()
TYPE =
∀n:nat.∀m:nat.(le n m)→(not (lt m n))
BODY =
assume n: nat
assume m: nat
suppose H: le n m
we proceed by induction on H to prove not (lt m n)
case le_n : ⇒
the thesis becomes not (lt n n)
by (lt_n_n .)
not (lt n n)
case le_S : m0:nat :le n m0 ⇒
the thesis becomes not (lt (S m0) n)
(IHle) by induction hypothesis we know not (lt m0 n)
we must prove not (lt (S m0) n)
or equivalently (lt (S m0) n)→False
suppose H1: lt (S m0) n
consider H1
we proved lt (S m0) n
that is equivalent to le (S (S m0)) n
by (le_trans_S . . previous)
we proved le (S m0) n
that is equivalent to lt m0 n
by (IHle previous)
we proved False
we proved (lt (S m0) n)→False
not (lt (S m0) n)
we proved not (lt m n)
we proved ∀n:nat.∀m:nat.(le n m)→(not (lt m n))